European Pepper Moth or Southern European Marsh Pyralid Duponchelia fovealis (Zeller) - Stephanie D. Stocks; Amanda Hodges (EDIS)
Researchers are monitoring this notable greenhouse pest in northern Europe and Canada for the cut flower, vegetable, and aquatic plant industries. Its native range is southern Europe, the eastern Mediterranean region, the Canary Islands, Syria, and Algeria, but it has expanded its range to include other parts of Africa and the Middle East, northwest India, Europe, Canada, and the United States. Recent survey detected adults in pheromone traps in 20 of the 26 Florida counties surveyed. This 11-page fact sheet was written by Stephanie D. Stocks and Amanda Hodges, and published by the UF Department of Entomology and Nematology, December 2011.